Swarms of chemically modified antiviral siRNA targeting herpes simplex virus infection in human corneal epithelial cells - Kalke Kiira; Lund Liisa M.; Nyman Marie C.; Levanova Alesia A.; Urtti Arto; Poranen Minna M.; Hukkanen Veijo; Paavilainen Henrik (Public Library of Science, 2025)
Herpes simplex virus type 1 (HSV-1) is a common virus of mankind and HSV-1 infections
are a significant cause of blindness. The current antiviral treatment of herpes infection relies
on acyclovir and related compounds. However, acyclovir resistance emerges especially in
the long term prophylactic treatment that is required for prevention of recurrent herpes keratitis.
Earlier we have established antiviral siRNA swarms, targeting sequences of essential
genes of HSV, as effective means of silencing the replication of HSV in vitro or in vivo. In this
study, we show the antiviral efficacy of 2´-fluoro modified antiviral siRNA swarms against
HSV-1 in human corneal epithelial cells (HCE). We studied HCE for innate immunity
responses to HSV-1, to immunostimulatory cytotoxic double stranded RNA, and to the antiviral
siRNA swarms, with or without a viral challenge. The panel of studied innate responses
included interferon beta, lambda 1, interferon stimulated gene 54, human myxovirus resistance
protein A, human myxovirus resistance protein B, toll-like receptor 3 and interferon
kappa. Our results demonstrated that HCE cells are a suitable model to study antiviral RNAi
efficacy and safety in vitro. In HCE cells, the antiviral siRNA swarms targeting the HSV
UL29 gene and harboring 2´-fluoro modifications, were well tolerated, induced only modest
innate immunity responses, and were highly antiviral with more than 99% inhibition of viral
release. The antiviral effect of the 2’-fluoro modified swarm was more apparent than that of
the unmodified antiviral siRNA swarm. Our results encourage further research in vitro and in
vivo on antiviral siRNA swarm therapy of corneal HSV infection, especially with modified
siRNA swarms.